Ronchi test for characterization of X‐ray nanofocusing optics and beamlines. (31st July 2014) - Uhlén, Fredrik; Rahomäki, Jussi; Nilsson, Daniel; Seiboth, Frank; Sanz, Claude; Wagner, Ulrich; Rau, Christoph; Schroer, Christian G.; Vogt, Ulrich
<x xml:space="preserve">Abstract</x> A Ronchi interferometer for hard X‐rays is reported in order to characterize the performance of the nanofocusing optics as well as the beamline stability. Characteristic interference fringes yield qualitative data on present aberrations in the optics. Moreover, the visibility of the fringes on the detector gives information on the degree of spatial coherence in the beamline. This enables the possibility to detect sources of instabilities in the beamline like vibrations of components or temperature drift. Examples are shown for two different nanofocusing hard X‐ray optics: a compound refractive lens and a zone plate.